To answer this question, we need to isolate x. For this, we can proceed as follows:
1. Subtract 1 from both sides of the equation:
![2x+1-1=7-1\Rightarrow2x=6](https://img.qammunity.org/2023/formulas/mathematics/college/du08a3ijjez917d1h2zbifstrsbv0qndsj.png)
2. Divide by two to both sides of the equation:
![(2x)/(2)=(6)/(2)\Rightarrow x=3](https://img.qammunity.org/2023/formulas/mathematics/college/y9pqlzk9uljzgglqvvtrcr74nitgkpxman.png)
Therefore, the value for x = 3. We can check this result, if we substitute this value in the original euq